Cryptic Genetic Diversity Is Paramount in Small-Bodied Amphibians of the Genus Euparkerella (Anura: Craugastoridae) Endemic to the Brazilian Atlantic Forest - Fusinatto, Luciana A.; Alexandrino, Joao [UNESP]; Haddad, Celio F. B. [UNESP]; Brunes, Tuliana O.; Rocha, Carlos F. D.; Sequeira, Fernando (Public Library Science, 2013)
Morphological similarity associated to restricted distributions and low dispersal abilities make the direct developing Terrarana frogs of the genus Euparkerella a good model for examining diversification processes. We here infer phylogenetic relationships within the genus Euparkerella, using DNA sequence data from one mitochondrial and four nuclear genes coupled with traditional Bayesian phylogenetic reconstruction approaches and more recent coalescent methods of species tree inference. We also used Bayesian clustering analysis and a recent Bayesian coalescent-based approach specifically to infer species delimitation. The analysis of 39 individuals from the four known Euparkerella species uncovered high levels of genetic diversity, especially within the two previously morphologically-defined E. cochranae and E. brasiliensis. Within these species, the gene trees at five independent loci and trees from combined data (concatenated dataset and the species tree) uncovered six deeply diverged and geographically coherent evolutionary units, which may have diverged between the Miocene and the Pleistocene. These six units were also uncovered in the Bayesian clustering analysis, and supported by the Bayesian coalescent-based species delimitation (BPP), and Genealogical Sorting Index (GSI), providing thus strong evidence for underestimation of the current levels of diversity within Euparkerella. The cryptic diversity now uncovered opens new opportunities to examine the origins and maintenance of microendemism in the context of spatial heterogeneity and/or human induced fragmentation of the highly threatened Brazilian Atlantic forest hotspot.